Mergers & acquisitions: The Asian way - Singapore Management University (Institutional Knowledge at Singapore Management University, 2017)
Professor Wan Wai Yee studies the laws that govern mergers and acquisitions in Asia’s fast-changing landscape. See the related publications: Mergers and Acquisitions in Singapore: Law and Practice Independent financial advisers' opinions for public takeovers and related party transactions in Singapore Regulating squeeze-out techniques by controlling shareholders: The divergence between Hong Kong and Singapore